Sex hormones in Malay and Chinese men in Malaysia: are there age and race differences? - Kok-Yong Chin; Ima-Nirwana Soelaiman; Isa Naina Mohamed; Fairus Ahmad; Elvy Suhana Mohd Ramli; Amilia Aminuddin; Wan Zurinah Wan Ngah (Clinics, 2013)
OBJECTIVES: Variations in the prevalence of sex-hormone-related diseases have been observed between Asian ethnic groups living in the same country; however, available data concerning their sex hormone levels are limited. The present study aimed to determine the influence of ethnicity and age on the sex hormone levels of Malay and Chinese men in Malaysia. METHODS: A total of 547 males of Malay and Chinese ethnicity residing in the Klang Valley Malaysia underwent a detailed screening, and their blood was collected for sex hormones analyses. RESULTS: Testosterone levels were normally distributed in the men (total, free and non-sex hormone-binding globulin (SHBG) bound fractions), and significant ethnic differences were observed (p<0.05); however, the effect size was small. In general, testosterone levels in males began to decline significantly after age 50. Significant ethnic differences in total, free and non-SHBG bound fraction estradiol levels were observed in the 20-29 and 50-59 age groups (p<0.05). The estradiol levels of Malay men decreased as they aged, but they increased for Chinese men starting at age 40. CONCLUSIONS: Small but significant differences in testosterone levels existed between Malay and Chinese males. Significant age and race differences existed in estradiol levels. These differences might contribute to the ethnic group differences in diseases related to sex hormones, which other studies have found in Malaysia.